"Wage growth must be offset by productivity growth" The determinants of real unit labour costs : a case of Singapore's manufacturing sector - Thomasz, Ryan Joel (2016)
Although unit labour costs (ULC) conventionally measures cost competitiveness, an estimation study that encompasses its determinants – real wages and the disaggregated drivers of labour productivity – remains an unexplored domain. Replicating Ordóñez et al.’s (2015) decomposition analysis of ULC into three determinants of real remuneration per worker growth, capital intensity growth, and total factor productivity growth, this report conducted Ordinary Least Squares (OLS) estimation as an empirical analysis of competitiveness. Secondary data on Singapore’s manufacturing sector over the period of 1985 to 2014 was then utilized to study the three model variations of the overall manufacturing sector, two-digit industries, and the manufacturing sector as categorized by firm size. The main findings highlighted that increases in real wages are sustainable only if it is offset by proportionate increases in capital intensity and total factor productivity. Additionally, the results showed empirical evidence for the complementarity effect in large firms which allows them to be more cost-efficient. The results reaffirm the conclusions of Ordóñez et al.’s (2015) and Idson and Oi (1999), and are in agreement with Singapore’s choice to restructure the economy to be manpower-lean and more capital-intensive to be more cost-competitive.